Validation tests of the W2020 energy levels of water vapor. (December 2021) - Campargue, A.; Mikhailenko, S.N.; Kassi, S.; Vasilchenko, S.
Highlights: Validation tests of the W2020 list of H2 16 O are performed by CRDS near 8200 and 13200 cm −1. Position differences largely exceeding the claimed W2020 position uncertainties are evidenced for a number of lines. Deficiencies in the MARVEL treatment of the W2020 transition database may explain the observed discrepancies. Higher accuracy line positions can be achieved in the 5690–8340 cm −1 region using a limited number of high quality sources available in the literature. Abstract: A decade ago, a task group of the International Union of Pure and Applied Chemistry performed an exhaustive collection and review of measured transitions, applied the MARVEL procedure, and derived recommended empirical energy levels for nine major water isotopologues. Very recently, using an improved methodology, the sets of empirical energy levels of H2 16 O, H2 18 O and H2 17 O were updated, leading to the so-called W2020 energy levels and transition wavenumbers [Furtenbacher et al. J. Phys. Chem. Ref. Data 49 (2020) 043103; 10.1063/5.0030680]. Here we present validation tests of the W2020 line list of H2 16 O against spectra recorded by cavity ring down spectroscopy (CRDS) referenced to a frequency comb (FC), newly obtained in the 8040-8630 cm −1 region. The recorded spectra are found in excellent agreement with previous high-quality studies available in the literature. While these literature sources were all incorporated in the transition database used to derive the W2020 energy levels, the direct superposition of the FC-CRDS spectra to the W2020 line list of H2 16 O shows a number of large disagreements. Cases where deviations largely exceed the W2020 claimed uncertainty on the transition frequencies are noted. In the considered spectral region, the resulting W2020 list is thus less accurate than some of the published original sources used to derive the W2020 energy levels. We conclude that the sophisticated global procedure and algorithm elaborated to identify and adequately weight inaccurate line positions among the large W2020 transition database do not always prevent less accurate data from "spoiling" higher quality data sources. The W2020 list of H2 16 O is also compared to newly recorded CRDS spectra in the 12970–13200 cm −1 region (corresponding to the region of the A-band of O2 ), where previous observations were very scarce. As in the previous region, substantial position deviations are evidenced, and in many cases, the W2020 error bars appear to be strongly underestimated. Graphical abstract: Image, graphical abstract